Myeloid-derived suppressor cells-guided mesoporous silica nanoplatform delivering a BET inhibitor exerts anticancer effects by reprogramming the immunosuppressive tumor microenvironment - Li-Chan Chang; Li Xu; Yin-Fen Liu; Chang-An Lin; Si-Han Wu; Wen-Pin Su (Chemical Engineering Journal, 2026)

Young adulthood adiposity in relation to all-cause and cause-specific mortality: a prospective study of 0.5 million Chinese adults - Lei Fan; Andri Iona; Shixian Feng; Gang Zhou; Huarong Sun; Pang Yao; Canqing Yu; Yiping Chen; Dianjianyi Sun; Pei Pei; Ling Yang; Mingshu Yan; et al. (Science Bulletin, 2026)

Catalytic hairpin assembly-assisted dual-enhanced SERS satellite nanocomplex for ultrasensitive detection of lipopolysaccharides in injection samples - Chan Huang; Xiuying Li; Xuan Zeng; Lingzhi Chen; Huabin Zhang; Xinjie Guo; Yiqun Chang; Wenshi Huang; Yichu Nie; Tianen Zhou; Jiaqi Yu; Jun Xu; et al. (Chemical Engineering Journal, 2026)

Optimizing quality and palatability in texture-modified foods: A cross-framework study using sweet potato-based formulations - Wen-Yi Chang; Yi-Chan Chiang; Bo-Kang Liou; Po-Hsien Li; Po-Yuan Chiang (Food Research International, 2025)

Streptococcus atopica sp. nov., Isolated from the Feces of a Toddler with Atopic Dermatitis - Chin-Kan Chan; Hui-Shan Wu; Li-Jyun Tsai; Yun-Shien Lee; Yu-Chung Chang; Hui-Chung Wu; Yi-Sheng Chen (Current Microbiology, 2025)

Chlamydia trachomatis disrupts host metabolism in primary cervical epithelial cells - Heng Choon Cheong; Muhammad Ihsan Rommel; Yi Ying Cheok; Yee Teng Chan; Ting Fang Tang; Sofiah Sulaiman; Chung Yeng Looi; Bernard Arulanandam; Li-Yen Chang; Won Fen Wong (World Journal of Microbiology and Biotechnology, 2025)

Dynamic WNT signaling controls differentiation of hematopoietic progenitor cells from human pluripotent stem cells - Mo Li; Keiichiro Suzuki; Mengge Wang; Christopher Benner; Manching Ku; Li Ma; Ladan Kobari; Na Young Kim; Nuria Montserrat; Chan-Jung Chang; Guanghui Liu; Jing Qu; et al. (Science China Life Sciences, 2025)

Long-term Storage Stability of Inhalable Phage Powder Formulations: A Four-Year Study - Mengyu Li; Wei-Ren Ke; Rachel Yoon Kyung Chang; Hak-Kim Chan (The AAPS Journal, 2025)
The growing potential of bacteriophage therapy as an alternative treatment for pulmonary infections caused by multidrug-resistant bacteria has been increasingly recognized. This study aimed to evaluate the long-term stability of spray-dried phage powder formulations for pulmonary delivery, focusing on both biological activity and physicochemical properties. Three phages, PEV1, PEV20, and PEV61, were selected for formulation based on their host range against clinical strains of Pseudomonas aeruginosa . Eight spray-dried formulations, developed with varying proportions of lactose as a stabilizer and leucine as a moisture protectant and powder dispersion enhancer, were stored under controlled conditions at 4°C/15% relative humidity (RH) and 20°C/15% RH for four years. Over this period, phage titers declined with reduction ranging from 0.97 log 10 in the most stable formulation to 2.49 log 10 in the least stable one. Formulations with higher lactose concentrations (70–80%) demonstrated better preservation of biological activity. While the overall particle morphology remained unchanged, some thread-like elongated features protruding from the particle surfaces were observed, particularly in powders stored at 20°C/15% RH. However, there was a decline in the fine particle fraction (FPF) 50 – 60% to 27—44%. These findings showed the potential of spray-dried phage powders as a viable option for long-term storage to retain bioactivity, but the aerosol performance can be compromised. Graphical Abstract

Bridging the mercury exposure threshold: Development and application of whole-cell biosensors incorporating biotransformation pathways - Xue-ying Liu; Yan Guo; Wen-qi Zhang; Jiao Bai; Bing-chan Ma; Li-ting Zhou; Chang-ye Hui (Environmental Research, 2025)

Exploring the influence of PCB exposure on neonatal birth outcomes and neurobehavioral development after 15 years of prohibition - Tzu-Hsuen Yuan; Chun-Ju Tai; Cheng-Hsien Tsai; Jien-Wen Chien; Akifumi Eguchi; Chih-Yun Li; Ching-Wen Lin; Chisato Mori; Chang-Chuan Chan (Environmental Pollution, 2025)

Streptococcus taoyuanensis sp. nov., a Novel Species Isolated from a Patient with Bacteremia - Chien-Yu Lee; Chin-Kan Chan; Yi-Sheng Chen; Yun-Shien Lee; Shih-Ting Lin; Yu-Chung Chang; Hui-Chung Wu; Jia-rong Zhang; Hong-yu Chen; Li-Ting Wang (Current Microbiology, 2024)

Self-assembly of protein-DNA hybrids dedicated to an accelerated and self-primed strand displacement amplification for reinforced serum microRNA probing - Guoqiao Huang; Chan Li; Rong Wu; Guohui Xue; Qiufeng Song; Linwen Lan; Chang Xue; Liang Xu; Zhifa Shen (Analytica Chimica Acta, 2024)

Spatial distribution of the critical mineral resource element titanium in China and its influencing factors - Wei Wang; Xueqiu Wang; Xuemin Liu; Bimin Zhang; Qinghua Chi; Dapeng Li; Jian Zhou; Hanliang Liu; Xinbin Cheng; Hui Wu; Chan Chang; Binbin Sun (Journal of Geochemical Exploration, 2024)

Characterising personal, household, and community PM2.5 exposure in one urban and two rural communities in China - Ka Hung Chan; Xi Xia; Cong Liu; Haidong Kan; Aiden Doherty; Steve Hung Lam Yim; Neil Wright; Christiana Kartsonaki; Xiaoming Yang; Rebecca Stevens; Xiaoyu Chang; Dianjianyi Sun; et al. (Science of The Total Environment, 2023)

Biomarkers of aging - Hainan Bao; Jiani Cao; Mengting Chen; Min Chen; Wei Chen; Xiao Chen; Yanhao Chen; Yu Chen; Yutian Chen; Zhiyang Chen; Jagadish K. Chhetri; Yingjie Ding; et al. (Science China Life Sciences, 2023)

Heat and park attendance: Evidence from “small data” and “big data” in Hong Kong - Tongping Hao; Haoliang Chang; Sisi Liang; Phil Jones; P.W. Chan; Lishuai Li; Jianxiang Huang (Building and Environment, 2023)

Exploring the Wenchuan earthquake fault through the accurate location of WFSD-4# Well using seismic reflection - Yang-Yang Feng; Chang-Qing Yu; Hai-Bing Li; Chen Qu; Chan Wu; Qi Wang; Su Luo; Jin-Peng Huang; Ghazi Rehana (Applied Geophysics, 2022)

The effect of environmental factors on spatial-temporal variation of heterobranch sea slug community in northern Taiwan - Ho Yeung Chan; Yen-Wei Chang; Li-Shu Chen; Kazuki Nishida; Yi Ta Shao (Frontiers in Marine Science, 2022)
Sea slug (Subclass Heterobranchia) biodiversity is an important element of marine coral reef communities. However, due to their small size and cryptic behavior, few studies have examined their spatiotemporal variation. Taiwan is in the middle of East Asia Island Arcs, where it is one of the hotspots of sea slug diversity. Meanwhile, the northeast coast of this island lies within the subtropical monsoon region, where the climate shifts from a warm southwest monsoon (SW: May to Sep) to a cold northeast monsoon (NE: Oct to Apr). Between the monsoons, distinct temperatures and currents result in different community structures. To understand how those environmental factors (i.e., monsoon season, diel period and water depth) influence sea slug species richness and assemblages, we surveyed these invertebrates monthly at both night and day by diving in a marine protection area (CJ) and at a nearby non-protected site (MR) from May 2020 to Apr 2021. We showed that the species composition in our sampling area was highly consistent with what was found in Okinawa and Pescadores island, but less similar to those in southern Taiwan or Hong Kong. On the northeast coast of Taiwan, sea slug number and abundance were both higher in CJ than MR, but biodiversity ( H’ ) and the species evenness index J ’ was lower in CJ than MR. Additionally, cluster analysis indicated that the sea slug assemblages differed between the two sites. Monsoon season significantly influenced both species richness and species assemblages, with species richness during SW being significantly higher than in the NE monsoon and species assemblages also being distinct between these two seasons. Moreover, species richness increased with water depth (within the surveyed range of 0-25 m). Diel period did not exert a strong impact on sea slug biodiversity, except for species richness at CJ, where it was higher during the day than at night. Our study suggested that changing currents between the monsoon seasons could transport individuals originating from either the north or south of these island arcs. Furthermore, temperature and food sources may differ between seasons and depths, thereby influencing sea slug assemblages in this region.

Evaluation of the Potential of the Hard Clam (Meretrix meretrix) Shell Which Can Be Used as the Bioindicator for Heavy Metal Accumulation - Yen-Ting Lin; Fang-Chi Chang; Ming-Tsung Chung; Ze-Kai Li; Chang-Chuan Chan; Ying-Sheng Huang; Kuo-Fang Huang; Yu-San Han (Fishes, 2022)
Clams, Meretrix meretrix, were one of the favorite aquatic products in Taiwan and the world. It was reported that the water pollutants such as heavy metals and chemicals might accumulate in the clam body and shell through filter-feeding behavior. Thus, the bivalves could be used as bioindicators in the aquatic environment. The present study analyzed 20 trace elements, Mg, Sr, Li, Cd, Ba, Mn, Al, U, Ti, Pb, Nd, B, S, Zn, Fe, P, Na, K, Cu, and Ni, in the shells of the clams collected from the wild coastal area and cultured ponds to evaluate which elements have the potential to be biomarkers. The concentrations of 20 elements were detected by Solution-Based Inductively Coupled Plasma Mass Spectrometry (SB-ICPMS). Among them, Cd, Al, U, Ti, Nd, S, and K were below the detection limit. The remaining elements were analyzed for accumulation. The levels of Zn, Fe, and Ni possess high variation in an identical environment; so, a PCA was conducted without these three elements to reduce noise. The PCA result proved that the clam could absorb specific trace elements from the habitat. After a period of time, the contents of the absorption in the shells of the clams living in an identical environment became more similar. The analyzed element, Pb, was not found with a special difference in this study. The levels of Na, Sr, Mg, B, Mn, P, Ba, Li, and Cu reflected different sampling sites, which suggested that these elements in the species M. meretrix had the potential to be used as biomarkers for assessing heavy metal accumulation in the environment.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Effects of Soil Amendments on Microbial Activities in a Typical Cd-Contaminated Purple Field Soil, Southwestern China - Wenqiang Wang; Fengwu Zhou; Yajun Chang; Jian Cui; Dongyi He; Jinmeng Du; Andy Chan; Dongrui Yao; Yong Li; Zhiyuan Chen; Khalil Kariman (Bulletin of Environmental Contamination and Toxicology, 2020)

Correction to: Genetic variant predictors of gene expression provide new insight into risk of colorectal cancer - Stephanie A. Bien; Yu-Ru Su; David V. Conti; Tabitha A. Harrison; Conghui Qu; Xingyi Guo; Yingchang Lu; Demetrius Albanes; Paul L. Auer; Barbara L. Banbury; Sonja I. Berndt; Stéphane Bézieau; et al. (Human Genetics, 2019)

Genetic variant predictors of gene expression provide new insight into risk of colorectal cancer - Stephanie A. Bien; Yu-Ru Su; David V. Conti; Tabitha A. Harrison; Conghui Qu; Xingyi Guo; Yingchang Lu; Demetrius Albanes; Paul L. Auer; Barbara L. Banbury; Sonja I. Berndt; Stéphane Bézieau; et al. (Human Genetics, 2019)

Sealed tube promoted coupling of camptothecin and norcantharidin acid ester and their preliminary biological activity evaluation in vitro - Xian H. Wang; Fu H. Yang; Chang K. Zhao; Lei Gao; Chan Li (Medicinal Chemistry Research, 2018)

Regulation of fine particulate matter (PM2.5) in the Pacific Rim: perspectives from the APRU Global Health Program - Chang-Fu Wu; Alistair Woodward; Ya-Ru Li; Haidong Kan; Rajasekhar Balasubramanian; Mohd Talib Latif; Mazrura Sahani; Tsun-Jen Cheng; Chia-Pin Chio; Nutta Taneepanichskul; Ho Kim; Chang-Chuan Chan; et al. (Air Quality, Atmosphere & Health, 2017)

A new cycloartane-type triterpenoid from the roots of Dianella ensifolia (L.) DC - Ben-Qin Tang; Chu-Wen Li; Jian-Bo Sun; Yu Chang; Judy Yuet-Wa Chan; Simon Ming-Yuan Lee; Bao Zeng (Natural Product Research, 2017)

Goatpoxvirus ATPase activity is increased by dsDNA and decreased by zinc ion - Ming-Liang Lee; Wei-Li Hsu; Chi-Young Wang; Hui-Yu Chen; Fong-Yuan Lin; Ming-Huang Chang; Hong-You Chang; Min-Liang Wong; Kun-Wei Chan (Virus Genes, 2016)

A genome-wide association study for colorectal cancer identifies a risk locus in 14q23.1 - Mathieu Lemire; Conghui Qu; Lenora W. M. Loo; Syed H. E. Zaidi; Hansong Wang; Sonja I. Berndt; Stéphane Bézieau; Hermann Brenner; Peter T. Campbell; Andrew T. Chan; Jenny Chang-Claude; Mengmeng Du; et al. (Human Genetics, 2015)

Porcine epidemic diarrhea virus uses cell-surface heparan sulfate as an attachment factor - Chang-chao Huan; Yue Wang; Bo Ni; Rui Wang; Li Huang; Xiao-feng Ren; Guang-zhi Tong; Chan Ding; Hong-jie Fan; Xiang Mao (Archives of Virology, 2015)

Establishment of an Agrobacterium-mediated genetic transformation procedure for the experimental model orchid Erycina pusilla - Shu-Hong Lee; Chia-Wen Li; Chia-Hui Liau; Pao-Yi Chang; Li-Jen Liao; Choun-Sea Lin; Ming-Tsair Chan (Plant Cell, Tissue and Organ Culture (PCTOC), 2015)

The combined effects of transforming growth factor-β and basic fibroblast growth factor on the human degenerated nucleus pulposus cells in monolayer culture - Erxing He; Ji Hao Cui; Chuang Li; Cheng Tang; In-Sung Kim; Young-Woo Kim; Ho-Guen Chang; Jae-Ryong Cha; Oh-Jong Byung; Yong-Chan Kim (Tissue Engineering and Regenerative Medicine, 2013)

Catalog of Erycina pusilla miRNA and categorization of reproductive phase-related miRNAs and their target gene families - Choun-Sea Lin; Jeremy J. W. Chen; Yao-Ting Huang; Chen-Tran Hsu; Hsiang-Chia Lu; Ming-Lun Chou; Li-Chi Chen; Chia-I Ou; Der-Chih Liao; Ysuan-Yu Yeh; Song-Bing Chang; Su-Chen Shen; et al. (Plant Molecular Biology, 2013)

The Effect of Osteochondral Regeneration Using Polymer Constructs and Continuous Passive Motion Therapy in the Lower Weight-Bearing Zone of Femoral Trocheal Groove in Rabbits - Nai-Jen Chang; Chih-Chan Lin; Chien-Feng Li; Kai Su; Ming-Long Yeh (Annals of Biomedical Engineering, 2013)

Significantly differential diffusion of neuropathological aggregates in the brain of transgenic mice carrying N-terminal mutant huntingtin fused with green fluorescent protein - Pei-Hsun Cheng; Chia-Ling Li; Lu-Shiun Her; Yu-Fan Chang; Anthony W. S. Chan; Chuan-Mu Chen; Shang-Hsun Yang (Brain Structure and Function, 2013)

Inhibition of Japanese Encephalitis Virus Infection by the Sulfated Polysaccharide Extracts from Ulva lactuca - Ya-Huang Chiu; Yi-Lin Chan; Tsung-Lin Li; Chang-Jer Wu (Marine Biotechnology, 2012)

Meta-analysis of new genome-wide association studies of colorectal cancer risk - Ulrike Peters; Carolyn M. Hutter; Li Hsu; Fredrick R. Schumacher; David V. Conti; Christopher S. Carlson; Christopher K. Edlund; Robert W. Haile; Steven Gallinger; Brent W. Zanke; Mathieu Lemire; Jagadish Rangrej; et al. (Human Genetics, 2012)

Pseudonocardia rhizophila sp. nov., a novel actinomycete isolated from a rhizosphere soil - Jie Li; Guo-Zhen Zhao; Hai-Yu Huang; Wen-Yong Zhu; Jae-Chan Lee; Chang-Jin Kim; Li-Hua Xu; Li-Xin Zhang; Wen-Jun Li (Antonie van Leeuwenhoek, 2010)

Polyphasic Taxonomy of Novel Actinobacteria Showing Macromolecule Degradation Potentials in Bigeum Island, Korea - Syed G. Dastager; Ashok Pandey; Jae-Chan Lee; Wen-Jun Li; Chang-Jin Kim (Current Microbiology, 2009)

Streptomyces mayteni sp. nov., a novel actinomycete isolated from a Chinese medicinal plant - Hua-Hong Chen; Sheng Qin; Jae-Chan Lee; Chang-Jin Kim; Li-Hua Xu; Wen-Jun Li (Antonie van Leeuwenhoek, 2009)

Proteolytic Activity from an Alkali-Thermotolerant Streptomyces gulbargensis sp. nov. - S. G. Dastager; Agasar Dayanand; Wen-Jun Li; Chang-Jin Kim; Jae-Chan Lee; Dong-Jin Park; Xin-Peng Tian; Q. S. Raziuddin (Current Microbiology, 2008)

Identification and phylogenetic analysis of orf virus from goats in Taiwan - Kun-Wei Chan; Jen-Wei Lin; Shu-Hwae Lee; Chih-Jung Liao; Meng-Chun Tsai; Wei-Li Hsu; Min-Liang Wong; Hung-Chang Shih (Virus Genes, 2007)

Association of Heart Rate Variability of the Elderly with Personal Exposure to PM1, PM1–2.5, and PM2.5–10 - Li-Te Chang; Chin-Sheng Tang; Ying-Zu Pan; Chang-Chuan Chan (Bulletin of Environmental Contamination and Toxicology, 2007)

Streptomyces tritolerans sp. nov., a novel actinomycete isolated from soil in Karnataka, India - Dastager G. Syed; Dayanand Agasar; Chang-Jin Kim; Wen-Jun Li; Jae-Chan Lee; Dong-Jin Park; Li-Hua Xu; Xin-Peng Tian; Cheng-Lin Jiang (Antonie van Leeuwenhoek, 2007)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Identification and phylogenetic analysis of orf virus from goats in Taiwan - Kun-Wei Chan; Jen-Wei Lin; Shu-Hwae Lee; Chih-Jung Liao; Meng-Chun Tsai; Wei-Li Hsu; Min-Liang Wong; Hung-Chang Shih (Virus Genes, 2007)

Transgenic tomato plants expressing an Arabidopsis thionin (Thi2.1) driven by fruit-inactive promoter battle against phytopathogenic attack - Yuan-Li Chan; Venkatesh Prasad; Sanjaya; Kuei Hung Chen; Po Chang Liu; Ming-Tsair Chan; Chiu-Ping Cheng (Planta, 2005)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)